Synthesis and antitumor activity of lapathoside D and its analogs - Panda, Parthasarathi (2013)
Phenylpropanoid sucrose esters are important class of plant-derived natural products and have greater potential to be leads for new drugs because of their structural diversity and broad-array of pharmacological and biological activities. Regio- and chemo-selective acylation of 2,1′:4,6-O-di-isopropylidene sucrose 4 with cinnamoyl chloride 5 and p-acetoxycinnamoyl chloride 6 afforded mono-, di-, tri- and tetra- variant PSEs in moderate yields. The first total synthesis of di-substituted PSE, lapathoside D 1′ has been achieved successfully in short and simple synthetic steps from sucrose 3 as an inexpensive starting material. Lapathoside D 1 and a set of selected synthesized PSEs were tested for in vitro cytotoxicity against human cervical epithelioid carcinoma (HeLa) cell lines. Most of the compounds exhibited significant antitumor activity with their IC50 values ranging from 0.05 to 7.63 μM. The primary screening results indicated that PSEs might be valuable source for new potent anticancer drug candidates.